Respuesta :

Answer:

Should be in the pic below

Step-by-step explanation:

Ver imagen weezer010902

Answer:

x = [tex]\frac{-3+\sqrt{19} }{2}[/tex] or x = [tex]\frac{-3-\sqrt{19} }{2}[/tex]

Step-by-step explanation:

We want to factor this. In order to factor it, we need to use the quadratic formula:

[tex]x=\frac{-b+\sqrt{b^2-4ac} }{2a}[/tex] or [tex]x=\frac{-b-\sqrt{b^2-4ac} }{2a}[/tex]

Here, a = 2, b = 6, and c = -5, so plug these in:

[tex]x=\frac{-6+\sqrt{6^2-4*2*(-5)} }{2*2}=\frac{-6+\sqrt{76} }{4} =\frac{-6+2\sqrt{19} }{4} =\frac{-3+\sqrt{19} }{2}[/tex]

AND

[tex]x=\frac{-6-\sqrt{6^2-4*2*(-5)} }{2*2}=\frac{-6-\sqrt{76} }{4} =\frac{-6-2\sqrt{19} }{4} =\frac{-3-\sqrt{19} }{2}[/tex]

Thus, the answers are x = [tex]\frac{-3+\sqrt{19} }{2}[/tex] or x = [tex]\frac{-3-\sqrt{19} }{2}[/tex].

Hope this helps!

ACCESS MORE